Acute myocardial infarction: Does survival depend on geographical location and social background?. (29th August 2020) - Kjærulff, Thora Majlund; Bihrmann, Kristine; Zhao, Jinfeng; Exeter, Daniel; Gislason, Gunnar; Larsen, Mogens Lytken; Ersbøll, Annette Kjær
Abstract: Aims: This study described the interplay between geographical and social inequalities in survival after incident acute myocardial infarction (AMI) and examined whether geographical variation in survival exists when accounting for sociodemographic characteristics of the patients and their neighbourhood. Methods: Ringmap visualization and generalized linear models were performed to study post-AMI mortality. Three individual-level analyses were conducted: immediate case fatality, mortality between days 1 and 28 after admission and 365-day survival among patients who survived 28 days after admission. Results: In total, 99, 013 incident AMI cases were registered between 2005 and 2014 in Denmark. Survival after AMI tended to correlate with sociodemographic indicators at the municipality level. In individual-level models, geographical inequality in immediate case fatality was observed with high mortality in northern parts of Jutland after accounting for sociodemographic characteristics. In contrast, no geographical variation in survival was observed among patients who survived 28 days. In all three analyses, odds and rates of mortality were higher among patients with low educational level (odds ratio (OR) (95% credible intervals) of 1.20 (1.12–1.29), OR of 1.12 (1.01–1.24) and mortality rate ratio of 1.45 (1.30–1.61)) and low income (OR of 1.24 (1.15–1.33), OR of 1.33 (1.20–1.48) and mortality rate ratio of 1.25 (1.13–1.38)). Conclusion: Marked geographical inequality was observed in immediate case fatality. However, no geographically unequal distribution of survival was found among patients who survived 28 days after AMI. Results additionally showed social inequality in survival following AMI.